2021
DOI: 10.1109/access.2021.3063856
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Jamming-Position Maneuver Algorithm of Off-Board Active Electronic Countermeasure Unmanned Surface Vehicles

Abstract: The existing off-board active decoys face such common technical problems as short action time, limited jamming power, and difficult control over deployment situation and effective directive jamming beam direction. For this reason, this paper introduces a new mode and process of anti-missile combat, which places the radar active decoy on an unmanned surface vehicle (USV) to collaborate with the surface warship during the off-board active anti-missile combat. Following the principles of radar terminal guidance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the case of Radar A, it can be observed that the wave path of the target echo is longer than that of jamming signal. Similar to outboard active decoy jamming [24], a delay module could be added on the jammer, which makes r2=r3 ${r}_{2}={r}_{3}$. For Radar B, the wave path of the target echo is shorter.…”
Section: Mathematical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Radar A, it can be observed that the wave path of the target echo is longer than that of jamming signal. Similar to outboard active decoy jamming [24], a delay module could be added on the jammer, which makes r2=r3 ${r}_{2}={r}_{3}$. For Radar B, the wave path of the target echo is shorter.…”
Section: Mathematical Analysismentioning
confidence: 99%
“…However, the symmetrical configuration of the inboard jammer provides prior knowledge helpful for the theoretical derivation [8,13,14,17,19], which does not hold in outboard jamming analysis. Meanwhile, analysis of outboard jamming is mainly about the active decoy, not the cross-eye jammer [24,25]. The more general outboard cross-eye jamming situation needed to be analysed to promote the application of unmanned platformbased cross-eye jamming.…”
Section: Introductionmentioning
confidence: 99%